Beyond Performance 2.0, 2nd Edition - Keller, Scott; Schaninger, Bill (Wiley, 2019)
Double your odds of leading successful, sustainable change Leaders aren't short on access to change management advice, but the jury has long been out as to which approach is the best one to follow. With the publication of Beyond Performance 2.0, the verdict is well and truly in. By applying the approach detailed by authors, Scott Keller and Bill Schaninger, the evidence shows that leaders can more than double their odds of success-from thirty percent to almost eighty. Whereas the first edition of Beyond Performance introduced the authors' "Five Frames of Performance and Health" approach to change management, the fully revised and updated Beyond Performance 2.0 has been transformed into a truly practical "how to" guide for leaders. Every aspect of how to lead change at scale is covered in a step-by-step manner, always accompanied by practical tools and real-life examples. Keller and Schaninger's work is distinguished in many ways, one of which is the rigor behind the recommendations. The underpinning research is the most comprehensive of its kind-based on over 5 million data points drawn from 2,000 companies globally over a 15-year period. This data is overlaid with the authors' combined more than 40 years of experience in helping companies successfully achieve large-scale change. As senior partners in McKinsey & Company, consistently named the world's most prestigious management consulting firm, Keller and Schaninger also draw on the shared experience of their colleagues from offices in over 60 countries with unrivaled access to CEOs and senior teams. Beyond Performance 2.0 also dares to go against the grain-eschewing the notion of copying best practices and instead guiding leaders to make choices specific to their unique context and organization. It does this with meticulously balance of focus on short- and long-term considerations, and on fully addressing the hard technical and oft cultural elements of making change happen. Further, the approach doesn't just focus on delivering change; it builds an organization's muscle to continuously change, making it healthier so that it can act with increased speed and agility to stay perpetually ahead of its competition. Leaders looking for a proven approach to leading large-scale change from a trusted source have found what they are looking for in Beyond Performance 2.0.